A New Approach to Innovation and its Application to the Countries of the European Union - Agüeros, Manuel; Casares-Hontañón, Pedro; Coto-Millán, Pablo; De Castro, Pablo; Pesquera, Miguel Ángel (Quaestiones Geographicae, 2013)
This research provides a new theoretical approach to innovation. Innovation relies on collaborative relationships between universities, private companies and public administration. This theoretical approach offers an opportunity for scientific discovery in an environment of collaboration. Innovative ideas are not self-contained items; they are more like ecosystems and networks. The article also provides data processed in recent years (2003-2009) for the European Union states, providing relevant empirical evidence on the relationship between human capital, relational capital, technological capital and innovation. In the econometric and statistical modelling, the countries of the Europe of the Fifteen (EU-15) will be considered.